(untitled) (Research, Society and Development, 2021)
Tuberculosis is an infectious disease of great public health importance, caused by Mycobacterium tuberculosis, being transmitted through aerosols expelled into the environment through speech, coughing or sneezing, coming from a previously infected individual. The objective of this study was to define an epidemiological profile of tuberculosis in the state of Piauí, from 2015 to 2020. It was a descriptive epidemiological study of historical, quantitative and documentary series, presenting an analysis of health. Data were obtained from the Notifiable Diseases Information System (SINAN), about notified cases of tuberculosis in people residing in the state of Piauí. There were records of 416 (9.01%) cases of death of people affected by tuberculosis, in the period 2015 to 2020, among these 168 (3.63%) were caused by tuberculosis and 251 (5.43%) by other causes. According to the data obtained in the system over the period studied, it is confirmed that the state of Piauí is an area with a high burden of tuberculosis, of accentuated transmission and that the disease is associated with the socioeconomic conditions of individuals, requiring better planning by the state health agencies. The work is intended to assist the National Plan for Tuberculosis Control and can serve as a basis to help improve strategies to combat and control the disease more effectively in the region of Piauí.